Perspectives of complementary and alternative medicine (CAM) practitioners in the support and treatment of infertility - O’Reilly, Erin; Sevigny, Marika; Sabarre, Kelley-Anne; Phillips, Karen P (Université d'Ottawa | University of Ottawa, 2014)
Abstract Background Infertility patients are increasingly using complementary and alternative medicine (CAM) to supplement or replace conventional fertility treatments. The objective of this study was to determine the roles of CAM practitioners in the support and treatment of infertility. Methods Ten semi-structured interviews were conducted in Ottawa, Canada in 2011 with CAM practitioners who specialized in naturopathy, acupuncture, traditional Chinese medicine, hypnotherapy and integrated medicine. Results CAM practitioners played an active role in both treatment and support of infertility, using a holistic, interdisciplinary and individualized approach. CAM practitioners recognized biological but also environmental and psychosomatic determinants of infertility. Participants were receptive to working with physicians, however little collaboration was described. Conclusions Integrated infertility patient care through both collaboration with CAM practitioners and incorporation of CAM’s holistic, individualized and interdisciplinary approaches would greatly benefit infertility patients.